Penerapan Aplikasi Geogebra pada Pembelajaran Matematika - Nurfadila Ulfa Siregar; Fitry Khairany Pulungan; Malika Thahara; Nabila Faiza Dalimunthe; Nurhabibi Fakhri; Neni Herawati; Ayu Rahmawati; Risna Mira Bella Saragih (Journal on Education, 2023)
From the research results, there is data that the use of computers in learning is still limited to the use of powerpoint. Mathematics teachers still face difficulties in making learning media and teaching materials. The solution offered is to provide GeoGebra application training to mathematics teachers to assist them in the process of learning mathematics. The purpose of this activity is to increase teacher and student understanding of the role of mathematics learning media and increase the knowledge and skills of teachers and students about good and explorative virtual learning media (mathlet). The method that will be carried out in this activity is through several stages, namely direct observation, interviews, presentations, and question and answer. The result of this activity is that teachers can improve the quality of the learning process in accordance with the current digital era. and knowledge gained in training, teachers are more creative and innovative in creating learning processes, teachers have understanding and knowledge of virtual learning media, teachers can use the GeoGebra application to create virtual learning media, teachers can create visual media, teaching materials, and assessment instruments relating to algebra and geometry.